Impact of uveal melanoma thickness on post‐plaque radiotherapy outcomes in the prophylactic anti‐vascular endothelial growth factor era in 1131 patients. (28th April 2020) - Yang, Xiaolu; Dalvin, Lauren A.; Mazloumi, Mehdi; Chang, Michael; Shields, Jerry A.; Mashayekhi, Arman; Shields, Carol L.
Abstract: Importance: The impact of tumour thickness on radiation complications following plaque radiotherapy for uveal melanoma in the anti‐vascular endothelial growth factor (VEGF) era remains unknown. Background: To evaluate treatment outcomes following plaque radiotherapy and prophylactic intravitreal bevacizumab for uveal melanoma based on initial tumour thickness. Design: This was a retrospective, interventional case series. Participants: Patients with uveal melanoma were included in this study. Methods: A review of medical records was conducted of patients with uveal melanoma treated with plaque radiotherapy and prophylactic intravitreal bevacizumab from 7 July 2000 to 2 November 2018. Main outcomes measures: Radiation‐related outcomes of cystoid macular oedema (CME), radiation maculopathy, papillopathy, retinopathy, iris neovascularization (NVI) and neovascular glaucoma (NVG) were compared based on tumour thickness (small [<3.0 mm] vs medium [3.1‐8.0 mm] vs large [>8.0 mm]). Results: Of 1131 eyes, 341 (30%) had small, 633 (56%) medium and 157 (14%) large melanoma. Comparison (small vs medium vs large) at 4 years following radiotherapy revealed large melanoma with greater Kaplan‐Meier estimated risk of CME (37% vs 37% vs 63%, P < .001), earlier onset of CME (33 vs 26 vs 19 months, P < .001) and greater development of NVI (<1% vs 2% vs 13%, P < .001) and NVG (1% vs 2% vs 12%, P < .001). Radiation‐induced maculopathy, papillopathy and retinopathy were not associated with tumour thickness. Conclusions and relevance: Compared with small and medium uveal melanoma, large uveal melanoma demonstrated greater 48‐month risk for CME, shorter time to CME onset and greater development of NVI and NVG following plaque radiotherapy and prophylactic intravitreal bevacizumab.